Vegetation Cover and Furrow Erosion due to Extreme Rain Events in Semiarid Environments - Cárceles-Rodríguez, Belén (2017)
The conservation of the soil resource in semi-arid environments is one of the major challenges of agricultural systems, particularly in the Mediterranean region. In the present study, two types of soil management were compared: minimum tillage (ML) and minimum tillage with spontaneous vegetation cover (MLVE). The comparison was conducted in a rainfed almond plantation at slope (35%), under an extraordinary event in 2015 (91.3 mm and EI30 of 2,719.89 mm ha-1 h-1). In this situation in MLVE plots, the development of furrows in contrast to ML were not recorded; the total soil loss was more than 12 times lower than that recorded in the latter. This fact demonstrated the effectiveness of the vegetal cover in the protection of the agricultural soil against the erosion during extreme events. Also, for ML management, furrow erosion represented more than 60% of the total soil loss, demonstrating the dominance of this type of erosion. Finally, it should be noted that this event represents the almost total loss of soil recorded in the experimental plots during the period 2012-2015; and this consequently shows the significant impact of extreme events on erosion rates in the Mediterranean region.